Combining brainstorming and modelling to improve students' writing skill: an action research at Phu Tho Centre for Foreign Languages and Information - Pham, Thi Ngoc Bich (University of Languages and International Studies, 2017)
This minor thesis was carried out with an attempt to improve students’ writing skill at Phu Tho Centre for Foreign Languages and Informatics. The thesis has the objectives of exploring the reasons for the students’ weak writing competence and justifying th (...)